Fundamentals of Geriatric Medicine A Case-Based Approach - Soriano, Rainier P.; Fernandez, Helen M.; Cassel, Christine K.; Leipzig, Rosanne M.; SpringerLink (Online service) (New York, NY : Springer New York, 2007)
As the population ages, the unique needs of elderly patients are becoming increasingly important to practitioners of primary care, geriatric medicine, family medicine, and internal medicine. Physicians need a handy resource that presents the essentials of geriatric medicine and suggests simple ways to provide better care. Experts in geriatric medicine have streamlined Cassel$1 (Bs classic text, Geriatric Medicine: An Evidence-Based Approach, Fourth Edition, into this concise guide filled with focused information and case-based instruction. This handbook addresses the complexity of disease prevention and presentation in elderly patients, as well as geriatric pharmacology. Medicare and Medicaid, and conditions common to elderly patients, including depression, dementia, and hypertension, are also covered. Numerous graphs and tables are included throughout the book to assist the reader in processing the information presented and incorporating it into clinical practice. This practical guide is an essential resource for all those caring for the elderly.s
Approach to the Older Adult Patient -- The Comprehensive Geriatric Assessment -- Geriatric Pharmacology and Drug Prescribing for Older Adults -- Sites of Care for Older Adults -- Medicare and Medicaid -- Psychosocial Influences on Health in Later Life -- Medicolegal Aspects of the Care of Older Adults -- Prevention and Chemoprophylaxis in the Elderly -- Vision and Hearing Impairments -- Exercise and Rehabilitation -- Nutrition -- The Older Surgical Patient -- Depression, Dementia, and Delirium -- Insomnia and Other Sleep Disorders -- Transient Ischemic Attack and Stroke -- Parkinson$1 (Bs Disease and Related Disorders -- Dizziness and Syncope -- Osteoarthritis -- Osteoporosis -- Instability and Falls -- Hip Fractures -- Hypertension -- Cardiovascular and Peripheral Arterial Diseases -- Diabetes Mellitus -- Thyroid Disorders -- Anemia in the Elderly -- Benign Prostatic Hyperplasia -- Erectile Dysfunction -- Urinary Incontinence -- Pressure Ulcers -- Overview of Palliative Care and Non-Pain Symptom Management -- Principles of Pain Management.s
Keywords: Medicine; General practice (Medicine).; Geriatrics; Primary care (Medicine).; Medicine & Public Health; Geriatrics/Gerontology.; Primary Care Medicine; General Practice / Family Medicine; Electronic books